2015
DOI: 10.1002/adfm.201503670
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanobipyramid‐Supported Silver Nanostructures with Narrow Plasmon Linewidths and Improved Chemical Stability

Abstract: Silver nanostructures with narrow plasmon linewidths and good chemical stability are strongly desired for plasmonic applications. Herein, a facile method is discussed for the preparation of Ag nanostructures with narrow plasmon linewidths and improved chemical stability through Ag overgrowth on monodispersed Au nanobipyramids. Structural evolution from bipyramid through rice to rod is observed, indicating that Ag atoms are preferentially deposited on the side surfaces of Au nanobipyramids. The resultant (Au na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 57 publications
3
129
0
Order By: Relevance
“…[1] As shown in Figure S13, the branched NCs display broad LSPR peaks in the visible-NIR spectral range.H ere,f inite-difference time domain (FDTD) simulations were used to investigate far-and near-field behavior of these structures.The plasmonic behavior of ab ranched decahedron is presented in Figure 7, with ab ranched pentatwinned rod and ab ranched icosahedron being analyzed in Figures S14 and S15, respectively.Branched decahedron, pentatwinned rod, and icosahedron models were constructed using the geometrical dimensions of the synthesized structures;h owever,t he models were treated as all-Au NCs due to limitations in simulating complex Au/Pd distributions. [24,25] Thesimulations of all-AuNCprovide aqualitative analysis of EF behavior of the synthesized branched NCs. TheL SPR features from the symmetry of the branched NCs are maintained, but the LSPR peaks occur at different energies with respect to their experimental analogues.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[1] As shown in Figure S13, the branched NCs display broad LSPR peaks in the visible-NIR spectral range.H ere,f inite-difference time domain (FDTD) simulations were used to investigate far-and near-field behavior of these structures.The plasmonic behavior of ab ranched decahedron is presented in Figure 7, with ab ranched pentatwinned rod and ab ranched icosahedron being analyzed in Figures S14 and S15, respectively.Branched decahedron, pentatwinned rod, and icosahedron models were constructed using the geometrical dimensions of the synthesized structures;h owever,t he models were treated as all-Au NCs due to limitations in simulating complex Au/Pd distributions. [24,25] Thesimulations of all-AuNCprovide aqualitative analysis of EF behavior of the synthesized branched NCs. TheL SPR features from the symmetry of the branched NCs are maintained, but the LSPR peaks occur at different energies with respect to their experimental analogues.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…TheL SPR features from the symmetry of the branched NCs are maintained, but the LSPR peaks occur at different energies with respect to their experimental analogues. [24,25] Thef ar-field (Figure 7a)a nd near-field (Figure 7e-j) plasmonic behavior was analyzed by changing the lights injection axis, k,a long the C 2 and C 5 rotational axis of the branched decahedron ( Figure S16). [3d,26] Figure 7reveals that the branched decahedron displays three major LSPR peaks:…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The simulations of all‐Au NC provide a qualitative analysis of EF behavior of the synthesized branched NCs. The LSPR features from the symmetry of the branched NCs are maintained, but the LSPR peaks occur at different energies with respect to their experimental analogues …”
Section: Resultsmentioning
confidence: 96%
“…The plasmonic behavior of a branched decahedron is presented in Figure , with a branched pentatwinned rod and a branched icosahedron being analyzed in Figures S14 and S15, respectively. Branched decahedron, pentatwinned rod, and icosahedron models were constructed using the geometrical dimensions of the synthesized structures; however, the models were treated as all‐Au NCs due to limitations in simulating complex Au/Pd distributions . The simulations of all‐Au NC provide a qualitative analysis of EF behavior of the synthesized branched NCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it has been shown that the edge of gold nanobipyramids (GBPs) are sharper than those of GNRs, which can yield local electric-field enhancements of GBPs 3 times larger than those of GNRs [4]. Thus substituting GNRs for GBPs should be beneficial in some applications [5,6], e.g. for photodynamic and photothermal therapies [7] probes for bio-applications [8], detection of influenza virus [9], surface-enhanced Raman scattering detection [10], as well as cancer cell imaging and photodynamic therapies [11].…”
Section: Introductionmentioning
confidence: 99%